EFL STUDENTS METACOGNITIVE STRATEGIES IN ONLINE-BASED LEARNING: IN RELATION TO THEIR WRITING QUALITY - Nur Ania Fitrianti; Arik Susanti (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2021)
This study aimed to investigate the correlation between students metacognitive strategies and their writing quality in an online learning context. It involved 35 English-major students at one of the state universities in East Java, Indonesia. A metacognitive strategies questionnaire and a writing rubric were used as the instruments of this study. Then, the data obtained were analyzed by using a descriptive statistic and a Spearman rho correlation analysis with SPSS 21 program. The results reported that the participants applied metacognitive strategies at high frequency. Among the three kinds of metacognitive strategies, evaluating strategies (M=4.17) are the most strategy used by students, followed by monitoring strategies (M=3.98) and planning strategies (M=3.92) sequentially. The overall mean of the students essay scores (M=76.10) reported that the students writing quality was a good level. The highest to the lowest quality was obtained by the organization aspect, mechanics, language use, vocabulary, and content respectively. Further, there was a moderate positive correlation between students metacognitive strategies and their writing quality in online learning. In sum up, the more students apply metacognitive strategies, the better writing quality they have. It is suggested to  conduct with larger participants to make the results more generalizable.